Checklist of the Acanthocephala in wildlife vertebrates of Mexico - García-Prieto, Luis; Garcia-Varela, Martín; Mendoza-Garfias, Berenit; de León, Gerardo Pérez-Ponce (Zootaxa, 2010)
Fifty four named and twenty three undetermined species of acanthocephalans associated with 213 wildlife vertebrate host species from Mexico are listed; they come from 220 localities, pertaining to 28 of the 33 Mexican states. The checklist contains information on their hosts, habitat, distribution, and records. In addition, three species of acanthocephalans (Polymorphus obtusus, Polymorphus trochus, and Southwellina dimorpha), are registered for the first time in Mexico, twenty six new locality records, and ten new host records are presented.